Validity and Reliability of the Persian Version of the PERception de la Scle’rose En Plaques et de ses Pousse’es Questionnaire Evaluating Multiple Sclerosis-related Quality of Life - Ghajarzadeh, Mahsa (Int J Prev Med, 2016)
BACKGROUND: Multiple sclerosis (MS) affects all aspects of patients. Recently, the “PERception de la Scle’rose En Plaques et de ses Pousse’es” (PERSEPP) scale was designed to assess MS-related relapse on quality of life (QoL). The aim of this study was to evaluate validity and reliability of Persian version of PERSEPP scale in Iranian patients with MS. METHODS: Two-hundred eleven patients with relapsing-remitting form of the disease asked to fill the PERSEPP scale, MSQOL-54, and SF-36 questionnaires. Fifty cases filed the questionnaire 2 weeks later to assess reliability. The intraclass correlation coefficient (ICC) and Cronbach's alpha analysis were used. RESULTS: Mean age and mean duration of disease were 32.2 ± 8.4 years and 6.5 ± 2.5 years, respectively. One hundred sixty-seven (79.1%) were female and 44 (20.9%) were male. Forty-one (19.4%) were in relapse phase of the disease. ICC score of all items was above 0.8. Cronbach's alpha of all items was above 0.8. The results show that the mean scores of four items (relationship difficulties, time perspective, and symptoms) were significantly different between cases in relapse and none relapse. Coping and relationship difficulties scores were significantly different between different expanded disability status scale groups. Pearson correlation score for QoL 54 and PERSEP calculated as r = 0.44, P < 0.001 and r = 0.66, P < 0.001 between SF36 and PERSEP. CONCLUSIONS: Persian version of PERCEPP questionnaire provides valid and reliable instrument to assess MS-related QoL.